Pelayanan Publik Berbasis Sistem Informasi Penatih (SIPENA) di Kelurahan Penatih Kecamatan Denpasar Timur - Ni Putu Aris Munikavila; Anak Agung Ayu Dewi Larantika (Universitas Warmadewa, 2022)
Public services in Penatih Village are conducted with web-based System Information Penatih (SIPENA). SIPENA program implementation conducted by Penatih Village is done to be able to provide public services that are fast, precise and accurate. The purpose of this research is to know and understand SIPENA-based public services and what factors become obstacles in SIPENA-based public services in Penatih Village. The approach used in this study is to use qualitative descriptive methods with the application of Edward III theory. Data collection is done by observation techniques, interviews, and documentation. The selection of informants is done by purposive sampling techniques, and qualitative data analysis is inductive. The results showed that the implementation of SIPENA program in the implementation of public services in Penatih Village has been running quite effectively. However, there are still several factors that become obstacles in the implementation of SIPENA program in Penatih Village regarding the content of policies, human resources support, facilities and infrastructure and communication.